1998
DOI: 10.1007/s002619900309
|View full text |Cite
|
Sign up to set email alerts
|

Lobar atrophy of the liver

Abstract: Lobar atrophy of the liver due to causes other than liver tumor or liver cirrhosis is a relatively rare pathological condition, and there are only a few reports in the literature. We report six such cases and try to evaluate the relationship between lobar atrophy and portal flow disturbance. The patients could be divided into two groups according to the site of the atrophy: those with atrophy of the left lobe (two cases) and those with atrophy of the right lobe (four cases). The two cases with atrophy of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…However, a recent clinical study has reported an asymptomatic marked hepatic lobar atrophy due to portal flow disturbance [8], and we must also consider the possibility that the hepatic deformity in our cases was related to impaired peripheral portal microcirculation, although the intrahepatic vascular system was grossly patent in all our cases.…”
Section: Discussionmentioning
confidence: 84%
“…However, a recent clinical study has reported an asymptomatic marked hepatic lobar atrophy due to portal flow disturbance [8], and we must also consider the possibility that the hepatic deformity in our cases was related to impaired peripheral portal microcirculation, although the intrahepatic vascular system was grossly patent in all our cases.…”
Section: Discussionmentioning
confidence: 84%
“…Some cases of lobar atrophy caused by hepatolithiasis and portal flow disturbances were reported, not necessarily linked to a malignant pathology [8]. However, the majority of cases of lobar atrophy described were caused by hilar cholangiocarcinoma [7], [9], [10].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, hepatic abnormalities usually described in situs ambiguous are: left-sided whole liver, middle-located whole liver and symmetric liver (isomeric liver) [1,8]. The pathogenesis of congenital agenesis of right lobe of the liver is not fully explained but it is thought to be an impaired mutual induction between the endodermal diverticulum and the diaphragm or abnormal development and thrombosis of the right portal vein during 2-3th week of embryologic growth [5,9]. It must be distinguished from severe atrophy of right hepatic lobe in cirrhosis, intrahepatic cholangiocarcinoma and compensatory hypertrophy of left hepatic lobe after a prior surgical resection of the right hepatic lobe.…”
Section: Discussionmentioning
confidence: 99%